2013
DOI: 10.1007/s12032-013-0586-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation and prognostic implication of Syk gene in human colorectal cancer

Abstract: The study was aimed to investigate the relationship between hypermethylation of Syk gene and clinicopathological characteristics and long-term outcomes in colorectal cancer. The effect of Syk on cell proliferation and invasion ability was also assessed. Methylation and expression status of Syk were explored in CRC tissues and cell lines by MSP, qRT-PCR and western blot assay. The effects of Syk overexpression on tumorigenesis were studied by in vitro assay. The correlation between Syk methylation and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Hypermethylation of the SYK promoter region, which may lead to complete silencing of the gene or to a decrease in its [3,9,17,18]. As of yet, it has remained unknown whether polymorphisms within the SYK gene promoter region may affect its transcription and/or may be associated with the risk to develop CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypermethylation of the SYK promoter region, which may lead to complete silencing of the gene or to a decrease in its [3,9,17,18]. As of yet, it has remained unknown whether polymorphisms within the SYK gene promoter region may affect its transcription and/or may be associated with the risk to develop CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and epigenetic changes that initiate and support the progression of CRC include inactivating mutations in DNA mismatch-repair genes, activating mutations in proto-oncogenes and mutations or aberrant methylation patterns resulting in the inactivation of tumor suppressor genes [2]. Of interest for the present study is the recent finding that lack of expression (both mRNA and protein) of the putative tumor suppressor gene spleen tyrosine kinase (SYK) correlates with an increased risk of CRC [3]. As yet, however, the mechanism underlying this association has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the pancreatic and lung cancer cells dependent on K-RAS (and SYK) for survival have a more epithelial morphology while K-RAS-independent cells that lack SYK have a mesenchymal morphology [70]. Decreases in the expression of SYK in more malignant, invasive tumor cells due to epigenetic silencing are also seen in bladder cancer [103], colorectal cancer [104], melanoma [105, 106], gastric cancer [107, 108], nasopharyngeal cancer [109], and hepatocellular carcinoma (HCC) [110]. Interestingly, SYK levels are controlled also at the protein level by CHK1, which is frequently overexpressed in HCC.…”
Section: Syk As a Tumor Suppressormentioning
confidence: 99%
“…The re-introduction of SYK into highly invasive breast carcinomas reduces cell motility [114], invasive growth [97] and slows tumor growth and inhibits metastases in animal xenograft models [97]. Similar reductions in cell migration and invasion are seen when SYK is re-expressed in SYK-negative hepatocellular carcinoma [110], colorectal cancer [104], melanoma [105, 106] and pancreatic adenocarcinoma [102]. Gene expression analyses of SYK-negative Panc1 cells identified significant changes in the expression of over 2000 genes resulting from the re-expression of SYK [102] including genes such as MMP2 that are required for invasive growth.…”
Section: Syk As a Tumor Suppressormentioning
confidence: 99%
“…It also plays an important role in the control of cell differentiation, proliferation and spread. Recent studies have found that Syk, as a tumor suppressor of PTKs, is closely related to tumor invasion and metastasis (Tatsuya et a1., 2003;Yang et al, 2013), and studies showed potential inhibitory effect of the gene Syk in breast, gastric and pancreatic cancer. A few literatures have been reported about Syk expression in lung cancer (Peng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%